Progress Report on the Five Year Plan for Bombay State 1953-54 - Planning Commission (Planning Commission, 1953)
The Plan for the Bombay State as originally framed in 1951-52 was estimated to cost Us. 146-31 crores. Government has spent about Rs. 82.07 crores up to the end of 1953-54 and made a further provision of Rs. 33.00 crores in the budget for the year 1954-55, thus bringing the total expenditure to about Rs. 1.15.07 crores at the end of four years of the Plan leaving about Rs. 31 crores to be found in 1955.56. In addition to the expenditure mentioned above, the State Government has spent or provided for about Rs. 5.4 crores on account of participation in schemes like Community 'Development Projects, National Extension Service and Local Development Works. Those schemes were not originally included in the State. Plan but have, been added later at the instance of the Centre which has agreed to bear a share in their cost. The details of the share of the expenditure borne by the State Government on these schemes are as follows
Bombay State